'FACT' AND 'FICTION' IN ROMAN HISTORICAL EPIC. (October 2014) - Manuwald, Gesine
<x content-type="archive" xml:space="preserve">Abstract</x> In the second half of the third century bce Roman historical epic (notably that written by Naevius and Ennius) and Roman historiography (notably that of Fabius Pictor) came into being at roughly the same time. Whether and in what ways these two literary forms may have mutually influenced each other in their early development is a matter of debate, but it is obvious that there are both similarities and a generic difference, demonstrated by the use of prose or verse respectively and the accompanying style. Such characteristics enable a distinction between different types of narrative, even if the same events in Roman history are covered.